The emerging therapeutic target of dynamic and reversible N6-methyladenosine modification during cancer development - Liu, Shougeng; Chen, Sihong; Tang, Chengfang; Zhao, Yingxi; Cui, Wei; Jia, Lina; Wang, Lihui (Frontiers in Oncology, 2022)
As a reversible and dynamic epigenetic modification, N6-methyladenosine (m6A) modification is ubiquitous in eukaryotic cells. m6A methylation is prevalent in almost all RNA metabolism processes that affect the fate of cells, including cancer development. As indicated by the available evidence, targeting m6A regulators may play a crucial role in tumor therapy and multidrug resistance. Currently, many questions remain uncovered. Here, we review recent studies on m6A modification in various aspects of tumor progression, tumor immunity, multidrug resistance, and therapeutic targets to provide new insight into the m6A methylation process.